MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MENGGUNAKAN PENDEKATAN SCIENTIFIC DENGAN MODEL COOPERATIVE LEARNING TIPE STAD - Nurul Azizah; M. Afrilianto; Asep Ikin Sugandi (IKIP Siliwangi, 2022)
The purpose of this study is to analyze the effect of applying a scientific approach through a cooperative learning model of the Student Teams Achievement Division (STAD) type on the mathematical problem solving ability of high school students on the subject matter of a three-variable linear equation system. The research used is classroom action research (CAR), with the subjects used are students of class X-IPS SMA Leppesa 2 Cililin with a total of 43 people. The instruments applied were in the form of test instruments, namely pretest and posttest, non-test instruments in the form of student and teacher activity observation sheets, and student response questionnaires related to learning. The data processing technique in this study is to see the percentage of students' completeness in each cycle. The results showed that there was an increase from the application of the STAD model scientific approach to students' mathematical problem solving abilities in the Three Variable Linear Equation System material.